Human rights, health and poverty reduction strategies (WHO GenevaCH, 2005)
Seeks to provide policy-makers with guidance, suggestions and real-life examples to help demonstrate how human rights can and have been applied to pro-poor health policies and initiatives, and how they can enhance the effectiveness of a poverty reduction strategy.
Keywords: HUMAN RIGHTS